RETRACTION NOTICE: Curcumin as an Anti-Proliferative Agent in Breast Cancer through RASSF1A, Bax, and Caspase-3 Protein - Nunung Ainur Rahma; Harliansyah; Fransiscus D. Suyatna; Mpu Kanoko; Primariadewi Rustamadji; Joedo Prihartono; Arleni Bustami; Samuel Johny Haryono; Bethy Suryawati Hernowo (Future Science, 2021)
Introduction: Curcumin is a polyphenol that has pharmacological activity that can inhibit tumor cell growth and induce apoptosis through various mechanisms. However, the specific mechanism of curcumin cytotoxicity remains controversial because of many anti- and pro-apoptotic signaling pathways in various cell types. This study aims to examine the relationship among curcumin on RASSF1A, Bax protein levels, and caspase-3 activity in supporting the apoptotic mechanism in CSA03 breast cancer cells. Method: Curcumin administration to cancer cells is based on differences in dosage with 24-hour incubation. Cytotoxicity after curcumin administration was determined using MTS. RASSF1A and Bax protein levels were tested through ELISA. Caspase-3 activity was used to determine apoptosis and was tested using flow cytometry. Results: The results indicated that curcumin had a cytotoxicity effect of 40.85 µg/mL. At concentrations of 40 µg/mL and 50 µg/mL, curcumin increases levels of protein RASSF1A (∆ = 26.53% and 47.35%, respectively), Bax (∆ = 48.79% and 386.15%), and caspase-3 (∆ = 1,678.51% and 1,871.889%) significantly. Conclusions: Curcumin exhibits anti-proliferative activity and apoptotic (Caspase-3) effects through activation of RASSF1A and Bax.